Convective Cloud Clusters and Squall Lines along the Coastal Amazon - Satyamurty, Prakki; Cândido, Luiz Antônio; Sousa, Aline Corrêa de (Monthly Weather Review, 2021)
Mesoscale convective cloud clusters develop and organize in the form of squall lines along the coastal Amazon in the afternoon hours and propagate inland during the evening hours. The frequency, location, organization into lines, and movement of the convective systems are determined by analyzing the ‘‘precipitation features’’ obtained from the TRMM satellite for the period 1998–2014. The convective clusters and their alignments into Amazon coastal squall lines are more frequent from December to July, and they mostly stay within 170 km of the coastline. Their development and movement in the afternoon and evening hours of about 14 m s21 are helped by the sea breeze. Negative phase of Atlantic dipole and La Niña combined increase the frequency of convective clusters over the coastal Amazon. Composite environmental conditions of 13 large Amazon coastal squall-line cases in April show that conditional instability increases from 0900 to 1200 LT and the wind profiles show a jet-like structure at low levels of the atmosphere. The differences in the vertical profiles of temperature and humidity between the large-squall-line composites and no-squall-line composites are weak. However, appreciable increase in the mean value of CAPE from 0900 to 1500 LT is found in the large-squall-line composite. The mean mixing ratio of the mixed layer at 0900 LT in La Niña situations is significantly larger in the large-squall-line composite. Thus, CAPE and mixed-layer mixing ratio are considered to be promising indicators of the convective activity over the coastal belt of the Amazon basin. © 2021 American Meteorological Society.
Keywords: Convection lines; Interannual variability